Cover Feature: A Semiconducting Cationic Square‐Grid Network with FeIII Centers Displaying Unusual Dynamic Behavior (Eur. J. Inorg. Chem. 14/2020). Issue 14 (8th April 2020) - Hudson, Timothy. A.; Sutton, Ashley L.; Abrahams, Brendan F.; D'Alessandro, Deanna M.; Davies, Casey G.; Goerigk, Lars; Jameson, Guy N. L.; Moubaraki, Boujemaa; Murray, Keith S.; Robson, Richard; Usov, Pavel M.; Yang, Guochun
Abstract : The Cover Feature shows an unusual 2D Fe III coordination network in which pairs of radical TCNQ anions are corralled within rectangular cavities. Electrical conductivity measurements reveal semiconducting behavior, which is supported by density functional theory calculations. Magnetic measurements are suggestive of weak antiferromagnetic coupling. Variable temperature Mossbauer spectroscopy indicates a rare example of the Goldanskii‐Karyagin effect, which, along with structural data, is consistent with concerted movement of Fe III centers within the crystal lattice. Image courtesy of Owen Abrahams. More information can be found in the Communication by B. F. Abrahams, G. N. L. Jameson, R. Robson et al.